2010
DOI: 10.1007/s00125-010-1686-z
|View full text |Cite
|
Sign up to set email alerts
|

Down’s syndrome in diabetic patients aged <20 years: an analysis of metabolic status, glycaemic control and autoimmunity in comparison with type 1 diabetes

Abstract: Aims/hypothesis Intellectual impairment in individuals with Down's syndrome and diabetes mellitus potentially limits the quality of diabetic control. In addition, these patients are at risk of having immunological abnormalities. The present study compared metabolic status and concomitant diseases in young (<20 years old) Down's syndrome patients with diabetes vs young type 1 diabetic patients. Methods The Diabetes-Patienten-Verlaufsdaten is a longitudinal follow-up database, which collects data from 298 German… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 13 publications
5
38
0
1
Order By: Relevance
“…A recent study of 159 DS children diagnosed with type 1 diabetes (DSD) demonstrated two peaks in diabetes incidence, one occurring before 2 years of age and the other in early adolescence. The mean age at onset in the 41,983 control subjects with type 1 diabetes was 8.42 years (8). These data suggest that diabetes occurring before 2 years of age in DS children may be etiologically different from type 1 diabetes.…”
mentioning
confidence: 76%
“…A recent study of 159 DS children diagnosed with type 1 diabetes (DSD) demonstrated two peaks in diabetes incidence, one occurring before 2 years of age and the other in early adolescence. The mean age at onset in the 41,983 control subjects with type 1 diabetes was 8.42 years (8). These data suggest that diabetes occurring before 2 years of age in DS children may be etiologically different from type 1 diabetes.…”
mentioning
confidence: 76%
“…The trisomy of chromosome 21 in individuals with Down syndrome provides a unique genetic landscape to assess gene function in organs other than the brain. The increased incidence of diabetes in Down syndrome individuals is indicative that a gene, or genes, on chromosome 21 could be essential to the maintenance of whole body glucose homeostasis and pancreatic β‐cell function. To this end β‐cell morphology and function were examined in fetal tissue from normal and Down syndrome donors .…”
Section: Endocrine Functionmentioning
confidence: 99%
“…We also thank Katharina Molz, Esther Molz, Andreas Hungele, and Martin de Souza (Epidemiology, University of Ulm) for help with data collection, integration, and analysis. In addition, we thank all pediatricians and family doctors in Germany for participation in the BABYDIAB study and Munich Family Study, as well as the patients, families, and physicians participating in the DPV initiative (for list of participating centers, see Rohrer et al ).…”
Section: Acknowledgementsmentioning
confidence: 99%